Interested Party Transactions in Joint Stock Companies under Russian and Foreign law: General Features - E. V. Kabatova; E. V. Vershinina; A. V. Lindo (Московский журнал международного права, 2011)
In the article we conduct a general comparative research on legal regulation of conflict of interests in joint stock companies in Russia and foreign countries, in particular England, USA, Germany and France. The sources of Russian and Foreign regulation of the matter are defined. The authors also give analysis of terminological distinction in regulation including Russian concepts of interested person, interested party transaction; as well as the notions used in English and American law: “conflict of interests”, “director’s conflicting interest transaction” respectively. The main types of interested party transactions under German and French company law are likewise introduced.